2018
DOI: 10.1186/s12941-018-0254-0
|View full text |Cite
|
Sign up to set email alerts
|

Application of antimicrobial drugs in perioperative surgical incision

Abstract: Infection in surgical incision often results in poor wound healing, and one of the main factors for wound infection is the use of antimicrobial agents. Rational use of antibiotics is one of the key factors to prevent incision infection in general surgery. The number of current clinical studies on antibiotic use before and during surgery is greater than that of systematic studies on antibiotic use after surgery. For the rational use of antibiotics and improvement of wound healing rate, researchers around the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
0
9
0
2
Order By: Relevance
“…If the prophylaxis is started at the wrong time, the patients will have inadequate serum and tissue concentrations of antibiotic at the time of incision and during the surgery. This, in turn, may lead to a greater risk of contamination and SSIs . We found that the correct dose of antibiotic was administered in 59 cases, whereas other patients received fewer doses than recommended.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…If the prophylaxis is started at the wrong time, the patients will have inadequate serum and tissue concentrations of antibiotic at the time of incision and during the surgery. This, in turn, may lead to a greater risk of contamination and SSIs . We found that the correct dose of antibiotic was administered in 59 cases, whereas other patients received fewer doses than recommended.…”
Section: Discussionmentioning
confidence: 85%
“…This, in turn, may lead to a greater risk of contamination and SSIs. 20,21 We found that the correct dose of antibiotic was administered in 59 cases, whereas other patients received fewer doses than recommended. This may be due to a lack of awareness of the updated recommendations (e.g.…”
Section: Discussionmentioning
confidence: 89%
“…Many studies had substantiated the same fact. [36][37][38] The percentage of drugs prescribed from non EML was found to be more in dermatology department. This may be due to the fact that wide variety of skin disorders presents to the OPD, which necessitates the use of drugs from non EML also.…”
Section: Discussionmentioning
confidence: 98%
“…Postoperative infections are a significant source of preventable perioperative morbidity and mortality, being a burden for patients’ quality of life and health care systems [22,23]. Prophylactic antibiotics have been used to prevent nosocomial infections but their effects are often impaired by the development of highly resistance bacterial strains [24,25,26]. To circumvent antibiotic resistance and provide postoperative infection prophylaxis, AgNPs were loaded within the HG as silver ions have strong antimicrobial activity, even against most resistant strains [27,28].…”
Section: Discussionmentioning
confidence: 99%